Influência de óleos vegetais no apressamento da maturação de figos (Ficus carica L) cv. "Roxo de valinhos" - Manica, Ivo; V R Pinheiro, Rubens; Condé, Alcides R; L Pinto , Geraldo (Revista Ceres, 2025)
A study was conducted in Viçosa, Minas Gerais, to determine the influence of vegetable oils on hastening the maturity of the ’Roxo de Valinhos’ variety of figs.